2017
DOI: 10.1163/22941932-20170160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Eucalyptus globulus and E. nitens wood and fibre quality

Abstract: An evaluation of 100 Eucalyptus globulus and 100 E. nitens trees (six years old) was made using the Pilodyn micro-drilling tool as an indicator of wood density. Thirty E. globulus and thirty E. nitens trees with high, medium and low density were selected and sampled with an increment borer at breast height for anatomical analysis using fibre tester equipment and the Resistograph device to generate detailed information about fibre biometry and anatomical wood properties of both species for hybrid development. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
3
14
0
2
Order By: Relevance
“…In a study of standing trees, Anna et al (2020) found a weak negative relationship between pin penetration depth and the density (r = −0.172) and the specific gravity (r = −0.282) in jabon wood. Carrillo et al (2017) also reported negative relationships between pin penetration values and basic wood density in Eucalyptus globulus (r = −0.53) and Eucalyptus nitens (r = −0.68). Stronger negative correlations between pin penetration depth and density and specific gravity were reported by Couto et al (2013) for Eucalyptus grandis and Eucalyptus urophylla and Carrillo et al (2017) for E. globulus and E. nitens.…”
Section: Relationship Between the Pin Penetration Depths At Three Wood Planes And The Physical Properties Of Woodmentioning
confidence: 85%
See 1 more Smart Citation
“…In a study of standing trees, Anna et al (2020) found a weak negative relationship between pin penetration depth and the density (r = −0.172) and the specific gravity (r = −0.282) in jabon wood. Carrillo et al (2017) also reported negative relationships between pin penetration values and basic wood density in Eucalyptus globulus (r = −0.53) and Eucalyptus nitens (r = −0.68). Stronger negative correlations between pin penetration depth and density and specific gravity were reported by Couto et al (2013) for Eucalyptus grandis and Eucalyptus urophylla and Carrillo et al (2017) for E. globulus and E. nitens.…”
Section: Relationship Between the Pin Penetration Depths At Three Wood Planes And The Physical Properties Of Woodmentioning
confidence: 85%
“…Carrillo et al (2017) also reported negative relationships between pin penetration values and basic wood density in Eucalyptus globulus (r = −0.53) and Eucalyptus nitens (r = −0.68). Stronger negative correlations between pin penetration depth and density and specific gravity were reported by Couto et al (2013) for Eucalyptus grandis and Eucalyptus urophylla and Carrillo et al (2017) for E. globulus and E. nitens. Stronger and weaker correlations between pin penetration depth and wood density or specific properties were presumably related to the number of tested samples and the uniformity of the sample conditions, especially in relation to moisture content.…”
Section: Relationship Between the Pin Penetration Depths At Three Wood Planes And The Physical Properties Of Woodmentioning
confidence: 85%
“…Couto et al (2013) reported the correlation between wood density and pilodyn penetration of the 42 months old E. grandis and E. urophylla were 0.00 and -0.44. Carrillo et al (2017) stated that the correlation between density and pilodyn on the 6 years old E. globulus and E. nitens was negative and strong. Similar results were reported by Shi-jun et al (2010) on 56 months old Eucalyptus, Warrier and Venkataramanan (2014) on 4 years old of Casuarina equisetifolia, Kien et al (2008) on 8 and 9 years old E. urophylla, and Kha et al (2012) on Acacia hybrid planted in Yen Tanh.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to process the Resi trace to extract other wood properties warrants investigation [94]. Likewise, the potential to extract annual ring widths and growth trajectories in plantation inventory has obvious value.…”
Section: Issues Related To Resistance Drillingmentioning
confidence: 99%